«Поэзия – уже перевод, с родного языка на чужой...» (Цветаева и Рильке) - НАДЬ, ИШТВАН (SlavVaria, 2021)
Poetry itself is translation from the mother tongue into another language… Cvetaeva’s letter to Rilke about the translation of poetry is Cvetaeva’s credo of translation. Cvetaeva constantly reflects on her own linguistic consciousness. The first extensive set of commentaries on translation appears in the poet’s correspondence with Rainer Maria Rilke. Cvetaeva developed the methaphor of “writing poetry as translating” inspired by wordplay in German: „Dichten ist schon nachdichten”. Translation is possible, because poetry is possible. Cvetaeva advocates an artistic, hermeneutically open approach to translation. Cvetaeva wrote in a letter to Rainer Maria Rilke: „Dichten ist schon übertragen, aus der Muttersprache – in eine andere, ob französisch oder deutsch wird wohl gleich sein.” Writing poetry is in itself translating, from the mother tongue into another language.